Diagnostic Efficacy of Bone SPECT Techniques in Differentiating Unilateral and Bilateral Condylar Hyperplasia - Luz Kelly Anzola; Natalia Venegas; Maria Clara Jaramillo; Sergio Moreno; Mauricio Hinojosa; Enrique Amador; Martin Orozco; Fernando Mut (Diagnostics)
Objectives: This analytical cross-sectional study evaluates diagnostic approaches for active condylar hyperplasia using bone SPECT techniques. Methods: it was compared the effectiveness of relative activity assessments between condyles and quantitative analysis using the condyle/clivus ratio. Results: This study’s findings reveal that the condyle/clivus ratio method significantly outperforms the relative uptake method, achieving a sensitivity of 90.1% (95% CI: 84.1–94) compared to 40.7% (95% CI: 33.5–48.2), and a specificity of 77.1% (95% CI: 67.4–85) versus 72.9% (95% CI: 62.9–81.5). The condyle/clivus ratio also showed a more favorable negative likelihood ratio of 0.13 compared to 0.82 for relative uptake, and a higher area under the curve (AUC) of 0.8360 versus 0.5679. Statistically significant differences were noted (p = 0.0001). The condyle/clivus ratio method effectively identifies affected condyles in unilateral and bilateral condylar hyperplasia cases. Conclusions: This study emphasizes the importance of incorporating comprehensive clinical evaluations and imaging modalities for assessing condylar growth activity, underscoring the need for tailored reference values in different populations to ensure reliable diagnostic interpretations.